Relevansi Nilai Sosial Al-Qur’an Terhadap Pembinaan Pergaulan Remaja: Studi Tafsir Al-Munir - Marfiyah Marfiyah; Enjang Burhanudin Yusuf (CV. ITTC INDONESIA, 2025)
This article aims to analyze the relevance of social values ​​in the Qur'an to fostering adolescent social relationships through a study of Wahbah az-Zuhaili's Tafsir Al-Munir. Adolescence is a critical phase in personality development, where environmental and social influences strongly shape thought patterns, behavior, and morality. Quranic social values ​​such as honesty, responsibility, politeness, justice, and self-care (iḥṣān) play a crucial role as guidelines in developing the character of Muslim adolescents. Using library research, this study examines Quranic verses related to social ethics and then analyzes Wahbah az-Zuhaili's interpretation of the Tafsir Al-Munir to identify a concept for fostering social relationships appropriate to the current context. The results of the study indicate that the Quranic social values ​​in the Tafsir Al-Munir are highly relevant for fostering healthy adolescent interactions, avoiding deviant behavior, and building social relationships based on noble morals. This research also confirms that internalizing the social values ​​of the Quran in education, particularly Islamic Religious Education (PAI), can be an effective strategy in shaping the character of civilized, responsible, and morally conscious adolescents. Thus, Tafsir Al-Munir makes a significant contribution as a normative reference for fostering adolescent social life in the modern era.